2003
DOI: 10.4049/jimmunol.171.6.2889
|View full text |Cite
|
Sign up to set email alerts
|

Activating and Inhibitory Ly49 Receptors Modulate NK Cell Chemotaxis to CXC Chemokine Ligand (CXCL) 10 and CXCL12

Abstract: NK cells can migrate into sites of inflammatory responses or malignancies in response to chemokines. Target killing by rodent NK cells is restricted by opposing signals from inhibitory and activating Ly49 receptors. The rat NK leukemic cell line RNK16 constitutively expresses functional receptors for the inflammatory chemokine CXC chemokine ligand (CXCL)10 (CXCR3) and the homeostatic chemokine CXCL12 (CXCR4). RNK-16 cells transfected with either the activating Ly49D receptor or the inhibitory Ly49A receptor we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 45 publications
(41 reference statements)
1
31
0
1
Order By: Relevance
“…The lack of TYK2 does not inhibit invasion of NK/NKT cells into the evolving lymphoma, since the numbers of NK and NKT cells in TYK2 -/-lymphoma were comparable to those in WT controls. Infiltration of immune cells into tumors is controlled by chemokine receptors, which activate JAK-STAT signaling cascades (42,43). Accordingly, our observations exclude a role for TYK2 in tumor invasion.…”
Section: Discussionmentioning
confidence: 62%
“…The lack of TYK2 does not inhibit invasion of NK/NKT cells into the evolving lymphoma, since the numbers of NK and NKT cells in TYK2 -/-lymphoma were comparable to those in WT controls. Infiltration of immune cells into tumors is controlled by chemokine receptors, which activate JAK-STAT signaling cascades (42,43). Accordingly, our observations exclude a role for TYK2 in tumor invasion.…”
Section: Discussionmentioning
confidence: 62%
“…Using a rat NK cell line transfected with LY49D or LY49A, Inngjerdingen et al have shown that ligation of LY49D increased migration toward CXCL10, whereas ligation of LY49A decreased migration. 12 Thus, CXCL10-transduced leukemia cell vaccines preferentially attract to the vaccine site NK cells that respond to this chemokine.…”
Section: Discussionmentioning
confidence: 99%
“…These chemokines attract activated T cells and natural killer (NK) cells. [11][12][13][14] CXCL10-deficient mice also had a defect in effector T-cell generation, indicating that CXCL10 might also be essential to T-cell adaptive immunity. 15 We therefore used the DA1-3b mouse model of AML to investigate if CXCL10 could induce an efficient antileukemic immune response.…”
Section: Introductionmentioning
confidence: 99%
“…6D). CXCL9 and CXCL10 chemokines were selected because they have been shown to be involved in the CTL-induced tumor regression in mice (26)(27)(28). Tumor samples of IL-13Ra2 DNA vaccine-treated mice collected on days 13 and 16 were positive for CXCL9 whereas control tumor samples were negative for this chemokine.…”
Section: Infiltration Of Cd4mentioning
confidence: 99%